The Legal Definition of Dangerous Driving in the Context of the Legislation on Administrative Offenses - Vladimir I. Maiorov; Oleg I. Beketov (Сибирское юридическое обозрение, 2017)
This article analyzes the introduction of the concept of «dangerous driving» in the Russian legislation. The definitions of dangerous driving enshrined in the laws of foreign countries as well as a mechanism of calling to account for this offense are considered. The Author notes that there are a number of institutional and legal issues which may arise in the implementation of this new regulation. The ways of how to address the mentioned problems and further perspectives of complementing and improving the dangerous driving rules are determined. Finally, the relevance of innovation was concluded despite its mixed assessment in the society.